Time-varying effect of oil price shocks on the stock market returns: Evidence from oil-importing and oil-exporting countries - Khaled Mokni (Energy Reports, 2020)
This paper performs a two-stage methodology based on the Structural VAR and time-varying parameter regression models to examine the dynamic reaction of a set of oil-related countries' stock markets to oil price shocks. Oil prices are studied by disentangling demand and supply shocks. Based on monthly data from the 1999-2018 period, the results report evidence of a time-varying reaction of all stock market returns to different oil shocks. Moreover, the stock returns react to the demand shocks more than to the supply shocks. Besides, the effect of supply shocks on stock returns is generally limited and negative, while the aggregate demand shocks exert a positive effect on almost all stock returns. Oil-specific demand shocks have positive effects on the oil-exporting stock returns and negative effects in the case of oil-importing countries, except for the Chinese market. These findings have important policy implications for policymakers and investors.
Keywords: C13; G10; G15; Q41; 330; Oil price shocks; Oil-exporting countries; Oil-importing countries; Stock returns; Time-varying regression